Improving Business Process Management Based on Benchmarking Principles - Baiyu, Li (Kharkiv : V. N. Karazin Kharkiv National University, 2024)
This master's thesis investigates the financial support system for science and technology innovation enterprises, focusing on the operations of ZY Bank in Henan Province, China. The study examines the role of banking institutions in supporting the sustainable development of innovative enterprises and their contribution to economic transformation. It analyzes the theoretical, methodological, and organizational aspects of business process management in financial institutions. Existing inefficiencies in financial service processes for innovation enterprises are identified, and optimization solutions are proposed. Practical recommendations are developed to improve the financial support system, enhance operational efficiency, and strengthen the competitiveness of the bank.

У магістерській роботі досліджено систему фінансової підтримки підприємств науково-технічних інновацій на прикладі діяльності банку ZY у провінції Хенань (Китай). Проаналізовано роль банківських установ у забезпеченні сталого розвитку інноваційних підприємств та їх вплив на економічну трансформацію. Розглянуто теоретичні, методологічні та організаційні аспекти управління бізнес-процесами у фінансових установах. Виявлено проблеми в процесах фінансового обслуговування інноваційних підприємств та запропоновано шляхи їх оптимізації. Розроблено практичні рекомендації щодо вдосконалення системи фінансової підтримки з метою підвищення ефективності та конкурентоспроможності банку.
Удосконалення управління бізнес-процесами на основі принципів бенчмаркінгу
Керівник роботи : Анна Олександрівна Крамаренко, кандидат економічних наук, доцент кафедри управління та адміністрування, Навчально-науковий інститут "Каразінська школа бізнесу"
Keywords: SOCIAL SCIENCES::Business and economics::Business studies; benchmarking; бенчмаркінг; management; менеджмент; business process; бізнес-процес; financialin stitutions; фінансові установи